Therapeutic Protocol for Orthosurgical Management of Class III Malocclusion in Patients With Cleidocranial Dysostosis. Issue 6 (September 2018) - Barth, Fernando André; Menuci Neto, Angelo; Almeida-Pedrin, Renata Rodrigues; Ladewig, Victor de Miranda; Conti, Ana Cláudia de Castro Ferreira
Abstract : Abstract: Cleidocranial dysostosis (CCD) is a congenital skeletal disorder with significant manifestations in facial and dental development. Patients are affected with CCD present maxillary deficiency, late dental eruption, and supernumerary teeth. Early and multidisciplinary approach is necessary to treat CCD patients, especially to manage dental eruption and Class III malocclusion with maxillary deficiency. Several orthodontic and surgical interventions are performed to enable traction and extraction of teeth. Yet the maxillary deficiency may be protracted followed by orthodontic dental compensation. On the other hand, it is important to note that CCD patients' treatment is closely related to the severity of transversal and sagittal deformities, as well as the discrepancies in the lower third of the face. In this context, patients with facial impairment highly affected by CCD may need ortho-surgical decompensation to reach more aesthetic outcomes. The present study reports a case of a 14-year-old young patient affected by CCD. Clinically, the patient presented Class III malocclusion, maxillary deficiency, short lower facial third, posterior crossbite, and anterior open bite leading to facial disharmony. The patient underwent treatment in 2 stages: the interceptive approach aimed to transversally expand the maxilla and promote its protraction; and the corrective phase combined with the orthognathic surgery treated the patients' main complains; the anterior open bite, unerupted teeth, and chin prominence. The treatment approach applied in the clinical report allowed the correction of the malocclusion and facial profile satisfying completely the patient's expectations.